Adoption, completion and continuance of MOOCs: a longitudinal study of students' behavioural intentions. Issue 3 (17th February 2022) - Gupta, Kriti Priya; Maurya, Harshit
ABSTRACT: The purpose of this study is to investigate the factors underlying the adoption, completion and continuance of massive open online courses (MOOCs), using technology-user-environment (TUE) framework, MOOCs features and MOOCs qualities. The proposed model was empirically tested using longitudinal research design. The primary data was gathered at three time points through a survey of 197 students at an Indian university. Stepwise regression analysis was used to test the hypothesised relationships in the proposed model. The results demonstrate that technological characteristics, user characteristics and MOOCs features influence the students' decisions in all the stages of MOOCs acceptance including initial adoption, completion and continuance. Environmental factors determine the students' initial intentions to adopt MOOCs, whereas MOOCs qualities predict their intentions to complete and continue the usage of MOOCs in future. Moreover, the intention to adopt MOOCs significantly predicts the intention to complete MOOCs which in turn significantly determines the intention to continue using MOOCs. These findings will be helpful for MOOCs providers and other stakeholders. The MOOCs providers can focus on the technological characteristics, user characteristics and MOOCs features as they carry a sustained influence on the students' intentions to adopt, complete as well as continue using MOOCs.